Phytochemical Screening and In-Vitro α-Glucosidase Inhibitory Activity Analysis of Ethanol Extract of Mangifera quadrifida - Fadilah, Fadilah (UI Scholars Hub, 2022)
Abstract Introduction: Type 2 Diabetes Mellitus (DM) is a metabolic disorder characterized by hyperglycemia caused by B cell dysfunction, insulin resistance, or both. Indonesia and worldwide have an increasing incidence that leads to a significant socio-economic burden. The effective treatment of Type 2 DM with minimal side effects is still challenging. This research aims to identify phytochemical properties in ethanol extract of Mangifera quadrifida and the effectivity as an alfa-glucosidase inhibitor beneficial to research on the treatment of type 2 DM. Method: Mangifera quadrifida was extracted by ethanol as solvent. The phytochemical analysis is conducted by phytochemical screening methods and thin-layer chromatography (TLC). The antidiabetic properties in ethanol extract of Mangifera quadrifida is tested by inhibitory activity on alpha-glukosidase. Result: The ethanol extract of Mangifera quadrifida contains tanin, triterpenoid, flavonoid, and glycoside. TLC test on the ethanol extract of Mangifera quadrifida was detected 4 points (Rf 0,15; 0,464, 0,511; and 0,63). The IC50 to α-glucosidase of Mangifera quadrifida and the acarbose as positive control are 18,19 ppm and 4,88 ppm respectively. Discussion: Tanin, triterpenoid, flavonoid, and glycoside of Mangifera quadrifida have antidiabetic properties. The result on IC50 value in ethanol extract of Mangifera quadrifida is among the active class of antidiabetic group although the value is higher the acarbose. Conclusion: Ethanol extract of the Mangifera quadrifida has phytochemical compunds that have antiadiabetic potential. Acarbose has better IC50 to α-glucosidase compared to Ethanol extract of Mangifera quadrifida.